Comparative study of flexural behaviour of carbon fiber reinforced polymer (CFRP) bars and strands - Fuli Ban; Thierno Aliou Ka; Yanze Peng; Shuai Guan; Jiahui Sun; Yue Liu; Kaiqiang Qin; Baiyong Fu; Sarkar Noor-E-Khuda; T. Tafsirojjaman (Polymer Testing)
Extensive research has been performed on the tensile properties of carbon fibre-reinforced polymer (CFRP) material used in both standalone and rehabilitation applications. Limited knowledge and design guidelines exist on the flexural behaviour of CFRP cable strands (herein strand) and reinforcing bars. This knowledge gap hinders the widespread use of strands and CFRP bars in prestressed structures and restricts their market share compared to reinforcing steel members. To address this gap, this study investigates the flexural behaviour of CFRP strands and reinforcing bars using a combination of experimental and numerical methods. A standard three-point bending test is employed to measure the flexural strength and ultimate curvature radius of strands and bars. The experimental study included strands of diameters 10.2 mm and 15.2 mm, and CFRP bars of diameters 9 mm, 12 mm, and 14 mm. Finite element analysis has been conducted to further investigate the flexural performance and failure mechanisms of the specimens. The test results indicate that the ultimate bending radius of the strands is approximately one-half of that of the bar, while their ultimate bending strength surpasses the bars by at least 10 %. Optimal lay lengths for the 10.2 mm and 15.2 mm cable strands are proposed based on the simulation results.